Definition of the European Lepidocyrtus curvicollis group (Collembola: Entomobryidae) with description of a new species from Sardinia (Italy) - Mateos, Eduardo; Petersen, Henning (Zootaxa, 2012)
The genus Lepidocyrtus was up to now represented by two species in Sardinia. However, recent molecular data suggestthe existence of several other species in the region. The study of a Lepidocyrtus population from the peninsula of CapoCaccia (NW Sardinia) has allowed the description of the species Lepidocyrtus apicalis sp. nov. Along with seven otherEuropean species, the new species constitute the “Lepidocyrtus curvicollis group”, characterized by the presence of scaleson the antenna, legs and dorsal side of manubrium, by having the mesothorax more or less protruded, labial seta M 1 shorterthan M 2 , presence of seta s on abd.IV, and by the dorsal macrochaetae formula R 0 R 1s R 1 So/00/0101+3. An identificationkey has been developed for differentiating all species of this group. With the new species the number of Lepidocyrtus species present in Sardinia increases to three and the number of total European Lepidocyrtus species to 30.